Urethral catheterization–associated urethral strictures in men at a tertiary hospital in Kigali, Rwanda: A cross-sectional study - Nzeyimana, Innocent; Bizumuremyi, Yves C.; Nyirimodoka, Alexandre; Rickard, Jennifer; Bonane, Alex (East and Central African journal of surgery, 2022)
Background Urethral catheterization is a risk factor for urethral stricture formation. Urethral strictures impact quality of life and increase medical expenses. We aimed to determine factors associated with catheter-induced urethral strictures among males treated at a university teaching hospital in Kigali, Rwanda. Methods We retrospectively reviewed the medical records of male patients whose urethral strictures were managed at a tertiary referral hospital in Kigali over a 1-year period. Follow-up data were collected for those found to have developed urethral catheterization– associated strictures. Results In 2016, 118 patients with urethral strictures consulted our hospital: 26 strictures (22.0%) were catheter induced, and 13 patients (mean age, 46 years; all male) provided follow-up data via questionnaire-guided interviews. The median symptom duration before consultation was 105 days (interquartile range [IQR], 12-544 days). The main reason of delayed presentation was delayed transfer from the district hospital (53.8%). Many patients (38.5%) attributed stricture development to trauma during catheterization, although most (76.9%) were unconscious during catheterization. Most catheterizations were done at referral hospitals (53.8% vs 38.5% done at district hospitals), and 46.2% were done in the emergency department. The main indication for catheterization was unconsciousness (53.8%), followed by monitoring of urine output (30.8%). The median duration of catheterization was 10 days (IQR, 7-23 days), and the median time between catheterization and onset of symptoms was 1 month (IQR, 3 weeks to 16 months). Conclusions Although preventable, catheter-induced urethral strictures continue to be burdensome. Healthcare professionals should avoid unnecessary catheterization. To avoid long-term complications, it is imperative to perform catheterization safely for those who require the procedure.